"Não vamos mais nos esconder": identidade-metamorfose-emancipação de uma bixa preta e suas implicações sexuais, raciais e regionais - Pires, Anderson Moraes (2023)
In this dissertation, which is part of the Subjectivity and Critique of the Contemporary research line of the Graduate Program in Psychology at the Federal University of Ceará, we discuss how the processes of metamorphosis and identity recognition of black homosexuals, especially those who call themselves “bixas pretas”, are taking place. Specifically, we discuss the construction and negotiation of identity at certain moments in life, such as adolescence and adulthood; and we learn about the intersectional implications of race, gender, sexuality and region in identity processes. We are interested in contexts that try to normalize identity policies based on white cis-heterosexuality. We asked ourselves: What are black queers or who are they, since identity politics, whether they refer to gender and/or sexuality or race, say that they are neither the center nor the margin? If such policies say what bixas pretas are (that they are not human), what is it possible to be other than non-human? We believe that bixas pretas have to face their own bodies as potential enemies and, as a result, have their identity elaborations hindered when they are recognized by presupposed identities. In other words, despite the violence that affects identities, there are processes of resistance, of life. In order to carry out the research, based on the studies on identity from Critical Social Psychology, we used Wendi's life story narrative as a conduit for our reflections and criticisms of the contemporary world. The interview with Wendi, which took place on a digital platform, was guided by the question “Who are you?”, without a structured script and/or questionnaire. In the analysis and discussions, we had to consider the historical, social and cultural aspects of our collaborator's life, as well as using intersectionality as a tool. We chose to organize the analyses of identity processes according to the characters Wendi experienced. Throughout the text, we articulate concepts from the fields of racial, gender and sexuality studies that have helped us, together with our theoretical framework, to highlight not only the processes of subalternization, marginalization and violence that surround the experiences of bixas pretas, but also the ways of life that resist, emancipate and dispute the possibilities of a dignified life that can be lived.